Organocatalytic synthesis of α,α–diaryl substituted α–amino acid derivatives by an interrupted three-component Ugi reaction - Glavač, Danijel (Array, 2019)
An organocatalytic interrupted three-component Ugi reaction for the synthesis of α,α–diaryl α–amino acid derivatives is described. The transformation proceeds with a range of isocyanides and 3-aryl isoindolinone alcohols using Brønsted acid catalysts to afford products in good to excellent yields. Based on the obtained results, a reaction mechanism is proposed and discussed.